DEMOKRATISASI PARTAI DAN DILEMA SISTEM KEPARTAIAN DI INDONESIA - Haris, Syamsuddin (Jurnal Penelitian Politik, 2006)
Politicalparties are integralpart o f process of democratization in Indonesia. But, rather be the solutionof the problem in democratization o f the country, Indonesian political parties are still part of the problem. Thepaper is aim to identify problem o f the parties in Indonesia and the party system. The paper describes that theparties have at leastfour shortcomings as its basicproblem, i.e. institutionalproblem, leadershipproblem, structuralproblem and ideological problem. This paper argues that to make political parties become the solution ofpoliticalproblem in Indonesia, it has to be modernized. In the context of revision o f Decree o f Political Party, the partysystem has to be fitted in with other system in Indonesian political system. The choice is not only to choosebetween multi-party or bi-party system, but to choose the system that coherence with the whole political system in Indonesia.